2019
DOI: 10.1002/jsfa.9708
|View full text |Cite
|
Sign up to set email alerts
|

Copper tolerance and antibiotic resistance in soil bacteria from olive tree agricultural fields routinely treated with copper compounds

Abstract: BACKGROUND Heavy metal pollution may act as persistent selective pressure that favors the spread of antimicrobial resistance in natural environments. The aim of this study was to isolate and identify metal‐tolerant bacteria from soils in olive tree fields routinely treated with copper‐derived compounds and to evaluate the tolerance of bacterial strains to other metals and their resistance to clinically relevant antibiotics. RESULTS Five hundred and ninety‐five bacterial isolates from 45 olive tree agricultural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 45 publications
0
15
1
1
Order By: Relevance
“…High levels of copper exposure may induce toxicity and the development of copper resistance in various pathogenic bacteria ( Altimira et al., 2012 ; Agga et al., 2014 ; Zhang et al., 2019b , 2019c ). Extensive use of copper in industry and mining and the widespread use of pesticides in agricultural production are major sources of copper pollution of soils and water ( Altimira et al., 2012 ; Glibota et al., 2019 ). Thus, the precise and tight regulation of copper levels in the body is required to prevent unwanted detrimental effects or dysbiosis in the host.…”
Section: Coppermentioning
confidence: 99%
“…High levels of copper exposure may induce toxicity and the development of copper resistance in various pathogenic bacteria ( Altimira et al., 2012 ; Agga et al., 2014 ; Zhang et al., 2019b , 2019c ). Extensive use of copper in industry and mining and the widespread use of pesticides in agricultural production are major sources of copper pollution of soils and water ( Altimira et al., 2012 ; Glibota et al., 2019 ). Thus, the precise and tight regulation of copper levels in the body is required to prevent unwanted detrimental effects or dysbiosis in the host.…”
Section: Coppermentioning
confidence: 99%
“…Pseudomonas and Variovorax are common indigenous flora in soil and water, both of which are associated with a variety of rare metabolic characteristics, including degradation of toxic and complex compounds [58]. Among them, Variovorax can complete a variety of catabolic pathways, has other characteristics related to the mediation of metal ions, organic sulphides, and other compounds [58], and exhibits resistance to multiple antibiotics [58,59]. Numerous studies have confirmed the contribution of compost application to vegetable microorganisms, especially to multi-resistant strains [28].…”
Section: Isolation and Identification Of Antibiotic Resistant Strainsmentioning
confidence: 99%
“…Heavy metal tolerant bacteria were isolated from soil samples of olive tree farms in a previous study [21]. Strain identification and antibiotic resistance phenotype were established [21] and the 96 strains used in the present study were selected according to soil source and metal tolerance [21].…”
Section: Strain Selectionmentioning
confidence: 99%
“…Application of copper-derived compounds in olive tree farms is a common practice in South Spain for prevention or treatment of infections caused by the fungus Spilocaea oleagina. Phenotypic metal tolerance and AR in bacteria from Cu-contaminated soils in olive tree farms was established in a previous study [21]. The purpose of this study was to evaluate the presence of genetic determinants for metal tolerance or AR in strains isolated from Cu-treated soils in the province of Jaén and classified as resistant to both type of compounds.…”
Section: Introductionmentioning
confidence: 99%